2014
DOI: 10.1007/s40279-014-0283-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Footwear on Running Performance and Running Economy in Distance Runners

Abstract: Certain models of footwear and footwear characteristics can improve running economy. Future research in footwear performance should include measures of running performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 55 publications
3
74
2
8
Order By: Relevance
“…With the recent development of minimalist shoes and barefoot running, numerous studies have investigated the effects of footwear on running economy and injury prevention. Despite the lack of consensus amongst the literature, the meta-analysis of Fuller, Bellenger, Thewlis, Tsiros, and Buckley (2014) provides support to the shoe mass influence on the running cost. For injury prevention, most of the positive biomechanical changes attributed to barefoot running pattern would result from the adoption of a forefoot contact and reduced impact peak (Hall, Barton, Jones, & Morrissey, 2013;Paquette, Zhang, & Baumgartner, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…With the recent development of minimalist shoes and barefoot running, numerous studies have investigated the effects of footwear on running economy and injury prevention. Despite the lack of consensus amongst the literature, the meta-analysis of Fuller, Bellenger, Thewlis, Tsiros, and Buckley (2014) provides support to the shoe mass influence on the running cost. For injury prevention, most of the positive biomechanical changes attributed to barefoot running pattern would result from the adoption of a forefoot contact and reduced impact peak (Hall, Barton, Jones, & Morrissey, 2013;Paquette, Zhang, & Baumgartner, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Time-trial measurements are desirable because they can be more easily related to race performance than sub-maximal tests of running economy. 1 The minimalist shoe group improved time-trial performance by an additional 21.1 seconds (95%CI: 0.4, 41.8 seconds) when compared to the conventional shoe group. This was considered a small ES in our cohort because time-trial time was highly variable (pooled SD: 87.0 seconds).…”
Section: Discussionmentioning
confidence: 90%
“…1 Some studies have suggested that wearing minimalist shoes (or racing flats) during running competition should be advantageous for running economy 1 and performance, 2 and runners have been doing this for many years. 3,4 However, a recent systematic review identified no studies investigating the effect of training in minimalist shoes on running performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current consensus in footwear biome-40 chanics literature is that running economy can be enhanced by footwear with appropriate mechanical characteristics (Sinclair, Taylor, Edmundson, Brooks, & Hobbs, 2014b). A variety of different shoe parameters including midsole cushioning, comfort, rearfoot control, midsole longitudinal stiffness, mass 45 and midsole viscoelasticity have been proposed to modify running economy (Fuller, Bellenger, Thewlis, Tsiros, & Buckley, 2014).…”
Section: Aq3mentioning
confidence: 99%